PRESENTATION: ABOUT THE NATURE OF MATHEMATICAL KNOWLEDGE - Serrano, José Manuel (Anales de Psicología / Annals of Psychology, 2008)
This work makes an analysis of the various investigations that are presented in this monograph number of Psychology of Mathematics and concludes that, directly or indirectly, all of them have in common the importance of declarative (know what), procedural (know how) and condi-tional (know when) knowledge, and through various algorithms of multi-plication, demonstrating the inseparability of these three types of knowl-edge in the domain of mathematics.